2013
DOI: 10.1159/000343621
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Syndrome and Cancer: From Bedside to Bench and Back

Abstract: As older patients present with an average of three comorbidities beside their cancer, geriatric oncology can provide unique clues to translational research in aging and cancer. We illustrate this approach with the example of the metabolic syndrome and cancer. Epidemiologic and clinical cohorts highlighted an association between the metabolic syndrome and a higher risk and worse prognosis of various cancers. In a bedside-to-bench transition, this led to an interest in analyzing the potential mechanisms underlyi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 98 publications
(90 reference statements)
0
8
0
Order By: Relevance
“…In recent years, researchers held that the tumorigenesis in the body was a systemic disease [ 3 ]. Thus, more and more attention was paid to dysfunction and abnormality of metabolism caused by the etiology and pathogenesis of tumor [ 4 ]. And accumulating evidence suggested that altered lifestyle and obesity were closely linked to an increased risk of lung cancer [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, researchers held that the tumorigenesis in the body was a systemic disease [ 3 ]. Thus, more and more attention was paid to dysfunction and abnormality of metabolism caused by the etiology and pathogenesis of tumor [ 4 ]. And accumulating evidence suggested that altered lifestyle and obesity were closely linked to an increased risk of lung cancer [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although the mechanisms are not fully understood, the importance of insulin resistance and hyperinsulinemia, as well as the role of insulin-like growth factor-1 (IGF-1) pathway, hyperglycemia, and production of toxic products such as advanced glycation dnd-products (AGEs) and reactive oxygen species (ROS) have emerged. These contribute to the occurrence of oxidative stress and cellular destruction, secretion of cytokines from adipocytes and other proteins with signalling properties, generally called adipokines, and chronic systemic inflammation, which accompanies obesity and leads to the production of inflammatory cytokines and the generation of tumorigenic environment [12][13][14][15][16].…”
Section: Mechanisms Linking Metabolic Syndrome To Cancermentioning
confidence: 99%
“…Recently, many researchers considered tumorigenesis process in the body as a systemic disease [ 3 ]. So, research attentions focused on the etiology and cause of cancer that lead to dysfunction and abnormality of metabolism increasingly [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%